Development of a high‐throughput glycoanalysis method for the characterization of oligosaccharides in human milk utilizing multiplexed capillary gel electrophoresis with laser‐induced fluorescence detection. Issue 16 (26th July 2013) - Kottler, Robert; Mank, Marko; Hennig, René; Müller‐Werner, Beate; Stahl, Bernd; Reichl, Udo; Rapp, Erdmann; Guttman, Andras
<x xml:space="preserve">Abstract</x> During the last decade, enormous progress regarding knowledge about composition and properties of human milk (HM) has been made. Besides nutrition, the three macro‐nutrients: proteins, lipids, and carbohydrates combine a large variety of properties and functions. Especially, complex oligosaccharides emerge as important dietary factors during early life with multiple functions. The characterization of these HM oligosaccharides (HMOS) within the total carbohydrate fraction is prerequisite to understand the relationship between milk composition and biological effects. Therefore, extended studies of large donor cohorts and thus, new high‐throughput glycoanalytical methods are needed. The developed method comprises sample preparation, as well as analysis of HMOS by multiplexed CGE with LIF detection (xCGE‐LIF). Via a respective database the generated "fingerprints" (normalized electropherograms) could be used for structural elucidation of HMOS. The method was tested on HM samples from five different donors, partly sampled as a series of lactation time points. HMOS could be easily identified and quantified. Consequently, secretor and Lewis status of the donors could be determined, milk typing could be performed and quantitative changes could be monitored along lactation time course. The developed xCGE‐LIF based "real" high‐throughput HMOS analysis method enables qualitative and quantitative high‐performance profiling of the total carbohydrate fraction composition of large sets of samples.